Role of Bihar Rural Livelihood Promotion Society in the Socio-Economic Development of Bihar: A Transformation from Semi-Feudal to Market-Driven Society (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Economic stagnation and widespread poverty, along with the prevalence of ‘semi-feudal' production relations, resulted in a large out-migration of agricultural laborers and impoverished peasants, mostly from north Bihar, on the one side. The Rural Livelihood Promotion Society in the Development of Socio-Economic Over the past 30 years, the rural Bihar labour market has altered dramatically. It has progressed from a sluggish, semi-feudal setting in which much labour was subjected to varying degrees of bondage to a more open, market-driven society.